Applicability of the ACE-III and RBANS Cognitive Tests for the Detection of Alcohol-Related Brain Damage - Brown, Pamela; Heirene, Robert M.; Gareth-Roderique-Davies,; John, Bev; Evans, Jonathan J. (Frontiers in Psychology, 2019)
Background and aims: Recent investigations have highlighted the value of neuropsychological testing for the assessment and screening of Alcohol-Related Brain Damage (ARBD). The aim of the present study was to evaluate the suitability of the Addenbrooke’s Cognitive Examination (ACE-III) and the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS) for this purpose. Methods: Comparing 28 participants with ARBD (11 with Korsakoff’s Syndrome and 17 with the umbrella “ARBD” diagnosis) and 30 alcohol-dependent participants without ARBD (ALs) we calculated Area Under the Curve (AUC) statistics, sensitivity and specificity values, base-rate adjusted predictive values, and likelihood ratios for both tests. Results: High levels of screening accuracy were found for the total scores of both the ACE-III (AUC = .823, 95% CIs [.714, .932], SE = .056; optimal cut-off ≤86: sensitivity = 82%, specificity = 73%) and RBANS (AUC = .846, 95% CIs [.746, .947], SE = .052; optimal cut-off ≤83: sensitivity = 89%, specificity = 67%) at multiple cut-off points. Removing participants with a history of polysubstance from the samples (10 ALs and 1 ARBD) improved the diagnostic capabilities of the RBANS substantially (AUC = .915, 95% CIs [.831, .999], SE = .043; optimal cut-off ≤85: sensitivity = 98%, specificity = 80%), while only minor improvements to the ACE-III’s accuracy were observed (AUC = .854, 95% CIs [.744, .963], SE = .056; optimal cut-off ≤88: sensitivity = 85%, specificity = 75%). Conclusions: Overall, both the ACE-III and RBANS are suitable tools for ARBD screening within an alcohol-dependent population, though the RBANS is the superior of the two. Clinicians using these tools for ARBD screening should be cautious of false-positive outcomes and should therefore combine them with other assessment methods (e.g., neuroimaging, clinical observations) and more detailed neuropsychological testing before reaching diagnostic decisions.